The development of band-stop filter for vibration control of a flexible manipulator using PIC microcontroller - Ng, Kai Bin (2009)
This thesis presents the development of band-stop filter f9r vibration control of a flexible manipulator using PIC micro controller. The simulation work is designed in Matlab based environment with sampling frequency of 1 kHz and the responses are presented in time and frequency domains. In this work, a single. link flexible manipulator that moves in a horizontal plane is considered. Modelling is done using the assumed mode method where two modal displacements are considered in characterizing the dynamic behavior of the manipulator incorporating structural damping in this .Project The band-stop filter is used to reduce vibrations in the system. This method reduce vibrations by filtering the natural frequencies that cause the system vibration This can improve vibration control done by bang-bang torque input control technique. It is then written into C code language, together with the bang-bang torque input, and compiled into .hex file to be programmed into a PIC microcontroller, PIC18LFK50. The band-stop filter that has been embedded into the PIC shows a similar result compared to the band-stop filter in Matlab. However, the PIC has its limitations, that is, it can only give output values which have two decimal places or below. This limitation has caused the hub angle of the flexible manipulator to increase throughout the end. The embedded filter in PIC also increases the processing time.